Team dynamics, running, and skill-related performances of Brazilian U11 to professional soccer players during official matches - Palucci Vieira, L. H.; Aquino, R.; Moura, F. A.; Barros, R. M. L.; Arpini, V. M.; Oliveira, L. P.; Bedo, B. L. S.; Pereira Santiago, P. R.; oliveira (The Journal of Strength and Conditioning Research, 2019)
Analyses of movements during soccer competition have been used previously to help develop conditioning programs. However, this has not been extensively studied in youth populations. Therefore, the purposes of this study were to examine (1) dynamics of collective tactical movements, (2) running, and (3) skill-related performances during soccer matches disputed by children to senior players. A total of 120 Brazilian players in the age groups U11, U13, U15, U17, U20, and professional (PRO) were monitored during official competition matches (N = 12). Using semiautomatic video-based tracking (30 Hz), match running variables including total distance traveled, average speed, maximum sprint speed, and high-intensity activities were evaluated. Tactical metrics were computed as team surface area, spread, and median frequency. Through notational analysis, technical skills such as involvements with the ball, passes, ball touches, duels, and goal attempts were also recorded. One-way analysis of variance and magnitude-based inferences were used to detect differences between ages. Although the average speed, team surface area, and spread tended to present stabilized increases from the U15 (e.g., U15 > U13 > U11), maximal sprinting speed (PRO > U17 > U15, U13, U11) and percentage at very high-intensity activities (U20 > PRO, U17 > U15 > U13 > U11) demonstrated continuous gains. Median frequencies were higher in the younger groups (U13, U15, U17 > U20, PRO), although the percentage of successful passes was higher in the older groups (PRO > U17, U15 > U13, U11). We concluded that Brazilian U11 to PRO players present different performance profiles for running, collective movement dynamics, and technical skills, and that the rate of development regarding these components varies. Coaches should be aware of these differences to select and adapt training content for each age group.